Kajian Tata Kelola dan Aksesibilitas Pembiayaan Menuju Keberlanjutan Perkebunan Kelapa Sawit Swadaya - Yanita, Mirawati; Ningsih, Rozaina (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
Independent smallholders contribute about 35 percent of Indonesia's total crude oil, but the smallholders' low output, consistently producing 45 percent less than plantation companies. This research aims to examine the governance and accessibility of independent smallholder financing for planters to the sustainability of palm oil farming. The method used is a survey method to obtain data and information related to the implementation of governance and accessibility of smallholder palm oil financing in Jambi Province. The results found that smallholders' palm financing's control and accessibility have not been implemented with measurable management. This is because smallholders often start their farming activities with less optimal planning ranging from the procurement of inputs such as uncertified seedlings and minimal maintenance related to capital limitations, let alone plants already entering old age. The consequence is lower productivity than national productivity. Non-governmental palm oil farmers have no bargaining power, and only as recipients of TBS prices are sold. The lack of mentoring also impacts garden management's limited knowledge and replaces old and damaged plants. Besides, access to financing from financial institutions also requires the land's legality, so various parties must deal with it. In the future, it is necessary to accelerate thinking and resources in real terms to demonstrate impartiality in helping non-governmental palm oil growers to ensure the sustainability of farming for the sake of shared prosperity.